On the use of register data in educational science research - Erik Mellander (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2016)
Register data are described, in general terms and in specific terms, focusing on informational content from an educational science perspective. Arguments are provided for why educational scientists can benefit from register data. It is concluded that register data contain lots of information relevant for educational science. Furthermore, two specific features of register data are considered: their panel data nature, implying that register data analyses under certain conditions can account for aspects on which the registers are not informative, and that they contain intergenerational links, facilitating the separation of genetic and environmental influences on learning. It is observed that while register data do not contain direct links between students and teachers this shortcoming can be overcome by merging register data with survey data on these links. Being population data, register data enable analyses which are not feasible to conduct by means of survey data. An illustration is provided of how quantitative and qualitative researchers can benefit from combining register-based statistical analyses with in-depth case studies. The use of register data in evaluations of causal effects of educational interventions is also described. To facilitate the exploitation of the aforementioned advantages, a discussion of how to get access to register data is included.
Keywords: 330; register data; Nordic; panel data; intergenerational links; ethical review; combining quantitative and qualitative methods; causal effect evaluations